«Bringing Militancy to Management»: An Approach to the Relationship between Activism and Government Employment since the Cristina Fernández de Kirchner Administration in Argentina - Vázquez, Melina (2014)
This article explores the relationship between employment in public administration and militant commitment, which is understood as that which the actors themselves define as «militant management». To this end, an analysis is presented of three groups created within three Argentine ministries that adopted «Kirchnerista» ideology: La graN maKro, the Juventud de Obras Públicas, and the Corriente de Libertación Nacional. The article explores the conditions of possibility and principal characteristics of this activism as well as the guidelines for admission, continuing membership, and promotion –both within the groups and government entities–; and the way that this type of militancy is articulated with expert, professional and academic capital as well as the capital constituted by the militants themselves.